Effect Of Evidence-Based Nursing Practices Training Programme on the Competency of Nurses Caring for Mechanically Ventilated Patients - Yousif Ghafel Latif Aldhafeeri, Jarallah Sawadi Rheel Aldhafeeri, Mohammad Fahhat Solabi Alenazi, Khaled Abdullah Soliman Alzabni, Ahmad Fahad Latif Aldhafeeri, Abdullah Haif Onaiber Aldhafeeri, Abdullaziz Hajjaj Onaiber Aldhafeeri (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Evidence-Based Practice (EBP) is globally recognized as a standard approach to improving healthcare quality and patient outcomes. Nurses, particularly those in Intensive Care Units (ICUs), play a crucial role in implementing EBP. Therefore, this study aims to assess the impact of an adapted evidence-based nursing practices training program on the competency of nurses caring for mechanically ventilated patients.Methods: A prospective open-label parallel 1:1  controlled trial was conducted involving 80 nurses from the National Hepatology and Tropical Medicine Research Institute, , caring for ICU patients. The trial, registered under NCT05721664, took place between November 2022 and February 2023. Nurses were randomly assigned to either the intervention group, receiving the evidence-based nursing practice training program (EBNPTP) based on the Johns Hopkins EBP conceptual model, or the control group, receiving traditional in-service education. Four assessments (one pre- and three post-assessments) were conducted using the adapted evidence-based nursing competency assessment checklist to measure competency levels over time. The primary outcome was an increase in competency levels among nurses caring for mechanically ventilated patients.Results: Statistically significant differences were observed between the intervention and control groups in terms of competency levels across the three post-assessments (p